Exercise for aging adults : a guide for practitioners - Sullivan, Gail M.; Pomidor, Alice K. (Springer, 2015)
This book translates the new findings in exercise research for the elderly for busy practitioners, trainees, students and administrators.℗ℓ This book provides practical strategies that can be implemented immediately in the common settings in which practitioners care for adults.℗ℓ The format includes key points and case examples which showcase the strong evidence supporting exercise by older adults as a key tool to enhance health, prevent serious outcomes, such as hospitalization and functional loss, and as part of the treatment plan for diseases that are common in older adults elderly with.℗ℓ Written by experts in the field of exercise in older persons, this book is a guide to maintaining quality of life and functional independence from frail to healthy aging adults.℗ℓ℗ℓ Strategies and exercises are discussed for specific care settings and illustrated via links to video examples, to ensure readers can immediately apply described techniques. ℗ℓ Exercise for Aging Adults: A Guide for Practitioners is a useful tool for physicians, residents in training, medical students, physical therapists, gerontology advance practice nurse practitioners, assisted living facility administrators, directors of recreation, and long-term care directors.